2012
DOI: 10.4040/jkan.2012.42.2.302
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Trends and Contents of Nursing Doctoral Dissertations in Korea

Abstract: Purpose: This study aimed to identify contents and trends of Korean nursing doctoral dissertations in terms of research methodology and theoretical characteristics. Methods: The design of the study was descriptive study and a total of 1,089 quantitative studies completed between 1982 and 2010 were reviewed using the analytical framework developed by the researchers. Results:The majority of studies utilized the experimental design (51.5%) and the others were survey design (38.8%) and methodological design (5.0%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
4
0
3
Order By: Relevance
“…The majority of the theses in this study were conducted in clinics. Similarly, Lee et al found that the majority of the theses in nursing were conducted in hospitals, and a lower number of theses were conducted in the field (12).…”
Section: Discussionmentioning
confidence: 96%
“…The majority of the theses in this study were conducted in clinics. Similarly, Lee et al found that the majority of the theses in nursing were conducted in hospitals, and a lower number of theses were conducted in the field (12).…”
Section: Discussionmentioning
confidence: 96%
“…A meta analysis conducted by Lee and friends among 1089 postgraduate theses written in 1982-2010 found out that most of the theses (51,5%) were designed experimental, 38,8% epidemiologic and 5% descriptive [12]. Shin and friends examined PhDtheses in the field of nursing in 2000-2006 and investigated that of theses 45% were experimental, 23% methodological and 17% descriptive [13].…”
Section: Discussionmentioning
confidence: 99%
“…• (Choe, et al, 2009;Kim et al, 2004;Lee, et al, 2012;Robinson & Dracup, 2008;Shin et al, 2008;Suh, et al, 2001;Yoon, et al, 2011). …”
Section: 회도서관을 비롯한 정부산하단체에서 1978년부터 1984년까mentioning
confidence: 99%
“…사실적으로 서술하였거나 Lee, 1986;Lee, Y. J., 2000;Lee, et al, 1991;Lee et al, 2011), 박사학위논문 분석을 중심으로 연구경향을 분석한 연구가 대부분이었다 (Choe, et al, 2009;Kim, et al, 2004;Lee et al, 2012;Park, et al, 2002;Shin, Sung, Jeong, & Kim, 2008;Yoon, Kim, & Yun, 2011). 1978년 • 우리나라 대학원 간호학 박사교육과정이 개설된 시대적 배 경과 영향요인을 통해 한국 간호학 박사교육의 역사적 의 미를 찾는다.…”
unclassified